ØªØ·Ø¨ÙŠÙ‚ Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…ØÙ„ÙŠØ© Ø¬Ø¨Ù„ Ø£ÙˆÙ„ÙŠØ§Ø¡ Ø¨ÙˆÙ„Ø§ÙŠØ© Ø§Ù„Ø®Ø±Ø·ÙˆÙ… - Febriani, Erma (Maharaat: Jurnal Pendidikan Bahasa Arab, 2018)
The needs of society in the field of education which is always developing every year, especially in the Arabic language curriculum, encourages researchers to do research on implementation of the Arabic language curriculum at Jabal Auliya' Locality, Khartoum, Sudan. The study aimed to know into what extent the curriculum was implemented for teaching Arabic language at Jabal Auliya' Locality, Khartoum State. Â This research was an analytical descriptive research involving 23 Arabic language teachers at Jabal Auliya'. Questionnaires were used to collect the data which were then classified and analyzed using statistics.Â The researcher concluded that the implementation of the Arabic language curriculum in Jabal Auliya' run well, but not yet maximal. The objectives contained in Arabic books are clear, the content and evaluation question contained in the book are in accordance with students' abilities, the teacher uses a variety of methods in teaching Arabic, but does not use a variety of instructional media, which causes learning not to run optimally, because the smooth application of learning models depends not only on the method used, but also on the learning media used.